Interconnecting the GCC states - El-Katiri, L (Oxford Institute for Energy Studies, 2011)
On 20 April 2011, the Gulf Cooperation Council (GCC) celebrated the inauguration of the UAE’s link to the GCC Interconnection Grid, an extensive 1200MW high-voltage system interlinking five of the six GCC countries’ national electricity networks. Originally conceived in the early 1980s, the project’s implementation and financing remained uncertain for two decades, until high windfall oil and gas revenues from the early 2000s and exploding power consumption rates finally prompted the GCC heads of state to officially proceed with the grid in 2004 and tender out construction contracts. Following the grid’s initial inauguration in July 2009, when Bahrain, Kuwait, Qatar and Saudi Arabia first ‘plugged in’ to one another, the recent link of the UAE to the grid constitutes another milestone in the project’s epic history. The only link left for completion is the one between the UAE and Oman, which is planned for 2013. This article explores the economic and political significance of the GCC Interconnection Grid for the region. Currently, the regional power grid serves only as a back-up mechanism supplying electricity-deficient countries with ad hoc electricity supplies. In the long term, however, the grid has the potential to effectively become a tool for commercial electricity trade between the GCC states and hence to help create a regional electricity market, also leading to far greater economic integration; that is, if GCC policy-makers continue to support regional institution building in the utilities sector, while also engaging in necessary domestic market reforms.